Revisiting the Postulates of Etiological Models of Eating Disorders: Questioning Body Checking as a Longer-Term Maintaining Factor - Opladen, Vanessa; Vivell, Maj-Britt; Vocks, Silja; Hartmann, Andrea S. (Frontiers in Psychiatry, 2022)
Body checking (BC) is not only inherent to the maintenance of eating disorders but is also widespread among healthy females. According to etiological models, while BC serves as an affect-regulating behavior in the short term, in the longer term it is assumed to be disorder-maintaining and also produces more negative affect. To date, most studies have investigated only short-term functions of BC and have neglected the theoretically proposed longer-term maintaining consequences. The present study therefore empirically examined the longer-term consequences of increased BC. In an online study with a crossover design, N = 167 women tracked their daily amount of BC over a total of seven days: Following a one-day baseline assessment of habitual BC, participants were asked to check their bodies habitually for three days and with a threefold increased frequency for three days, with a four-day washout period in-between. Before and after each BC episode, the impact of BC on affect, eating disorder symptoms, and general pathology was assessed, along with the number of different functions of BC that were endorsed. In line with the theories on eating disorders, participants showed longer-term consequences of increased BC in terms of increased negative affect and general pathology, while eating disorder symptoms remained unaffected. Contrary to the model assumptions, in the case of habitual BC, participants showed decreased general pathology and anxiety in the longer term. Furthermore, the endorsement of a higher number of BC functions led to increased negative affect and an increased amount of habitual BC, although again, there were no effects on eating disorder symptoms. The findings support the theoretically assumed role of maladaptive BC in maintaining negative emotion in the longer term. However, with the need for replication, our finding of positive effects of habitual BC on general pathology calls into question the overall dysfunctionality of BC among non-clinical women who are not at risk of developing an eating disorder.